Roger Raveel en Beervelde. - Jooris, Roland; Jooris, Roland (Tielt : Uitgeverij Veys, 1979)
Raveel, Roger ; Lucassen, Reinier ; De Keyser, Raoul ; Elias, Etienne
2 ex. : ned. + frans.
biog. p. 133
Nederlands & Frans
boek
Keywords: Raveel, Roger